Variant mapping and mutation discovery in inbred mice using next-generation sequencing. (December 2015) - Gallego-Llamas, Jabier; Timms, Andrew; Geister, Krista; Lindsay, Anna; Beier, David
Abstract Background The development of powerful new methods for DNA sequencing enable the discovery of sequence variants, their utilization for the mapping of mutant loci, and the identification of causal variants in a single step. We have applied this approach for the analysis of ENU-mutagenized mice maintained on an inbred background. Results We ascertained ENU-induced variants in four different phenotypically mutant lines. These were then used as informative markers for positional cloning of the mutated genes. We tested both whole genome (WGS) and whole exome (WES) datasets. Conclusion Both approaches were successful as a means to localize a region of homozygosity, as well as identifying mutations of candidate genes, which could be individually assessed. As expected, the WGS strategy was more reliable, since many more ENU-induced variants were ascertained.